The burden of opportunistic-infections and associated exposure factors among HIV-patients admitted at a Botswana hospital - Tlhakanelo, John T.; Mulumba-Tshikuka, Jose G.; Molefi, Mooketsi; Magafu, Mgaywa G. M. D.; Matchaba-Hove, Reginald; Masupe, Tiny (Jacobs Publishers, 2016)
Botswana is among countries most affected by the human immunodeficiency virus (HIV) pandemic. Since 2001, aggressive interventions have been launched by the government including free access to combination antiretroviral treatment (cART). cART is known to reduce HIV transmission, related morbidities and hospital admissions among people living with HIV (PLWH). However, hospital admissions among PLWH in Botswana still remain high. Factors associated with such admissions have not yet been highlighted. Even though opportunistic infections (OIs) have been incriminated as the major cause of admissions among PLWH, the OIs have not yet been meticulously studied in Botswana.